The Masters’ Control: How Ownership Structure Influences the Communication of Financial Ratios - Aripin, Norhani; Ho, Pauline; Tower, Greg (Asian Journal of Business and Accounting, 2017)
This study analyses the effect of the attributes of ownership structure and corporate governance on financial ratios disclosure in Malaysian listed firms’ annual reports over two key periods, 2001 and 2006. Overall, the extent of financial ratios disclosure has significantly increased from 12.2 per cent to 15.0 per cent. The highest level of financial ratios disclosure is for the sub-categories of Profitability, Cash Flow and Share Market Measures, whereas there is less information reported for Capital Structure and Liquidity ratios. Further, the analysis shows that the institutional ownership negatively influences the financial ratios disclosure for 2001; and foreign ownership is positively associated with financial ratios disclosure in 2006. Interestingly, family ownership appears to have no significant influence on the disclosure in either period. Ownership concentration, on the other hand has a positive association with financial ratios disclosure in 2001; this is the opposite direction than hypothesised. In addition, the corporate governance attributes have also influenced the financial ratios disclosure in 2001. As for control variables, firm size and profitability are found to have a positive relationship with financial ratios disclosure for both years. These findings provide evidence that the attributes of ownership structure and the implementation of sound corporate governance reduce the information asymmetry between management and stakeholders and therefore, further enhance transparency. Keywords: Corporate Governance, Financial Ratios Disclosure, Malaysia JEL Classification: M41, G32